2022
DOI: 10.1037/aca0000322
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of creativity in young people: Using frequentist and Bayesian approaches in estimating the importance of individual and contextual factors.

Abstract: The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we will investigate on a case-by-case basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 96 publications
(179 reference statements)
0
5
0
Order By: Relevance
“…Feist (1998) also found a similar effect using a meta-analysis of studies focusing on artists and scientists. Several other studies have confirmed the relationship between openness and extraversion with divergent thinking performance (Carson et al, 2003;Dumas et al, 2020a;Asquith et al, 2022).…”
Section: Introductionmentioning
confidence: 75%
“…Feist (1998) also found a similar effect using a meta-analysis of studies focusing on artists and scientists. Several other studies have confirmed the relationship between openness and extraversion with divergent thinking performance (Carson et al, 2003;Dumas et al, 2020a;Asquith et al, 2022).…”
Section: Introductionmentioning
confidence: 75%
“…Openness is highly correlated to creativity across a wide variety of measures (Feist et al, 2017). These extend to self-reported creative activities (Jauk et al, 2014), creative selfefficacy (Karwowski et al, 2013), divergent thinking performance (Asquith et al, 2022), and rated creative products (Maslej et al, 2014). It is important to note that because most measures of openness are reliant on questions about imagination and esthetics, these types of connections are not necessarily surprising (Martindale, 1989).…”
Section: Blue: Personality and Cognitionmentioning
confidence: 99%
“…The first method considered an overall originality score including all the items generated. This average originality score was calculated from the proportional weighting of each use by the frequency of its occurrence [57,58]. To maintain high originality as indicative of high divergent thinking, and to resolve the confounding influence of fluency on originality (i.e., those with high fluency score having a high originality score as a result of more uses being summed in the calculation) [59], this single score was then divided by the fluency score of the participant and subtracted from 1 (e.g., 1 -(.42/4)), resulting in a difference score (e.g., .90), which was referred to as the average originality score.…”
Section: Plos Onementioning
confidence: 99%
“…(c) Peak originality scoring (objective): This method only considered responses of high originality as evidenced by the statistical rarity of the responses within the sample [57,58]. The proportional weighting (i.e., number of times the use was generated in the sample / total number of participants) of each use was converted into a percentage (e.g., 0.17 = 17%).…”
Section: Plos Onementioning
confidence: 99%